Analisis Implementasi EMIS: Meningkatkan Layanan Administrasi dan Pengembangan Guru Profesional di Madrasah - Umaroh, Yeni; Tuala, Riyuzen Praja; Irwandani, Irwandani (STMIK Banjarbaru, 2025)
This study aims to analyze the implementation of Education Management Information System (EMIS) in Madrasas, identify challenges in implementation, and evaluate its impact on administrative services and teacher professional development. This study uses a mixed-method method with a sequential explanatory approach. Quantitative data was collected through questionnaires and analyzed using correlation tests, while qualitative data was obtained through interviews to deepen the research findings. The results of this study show that Education Management Information System improves administrative efficiency, reduces recording errors by up to 35%, and accelerates decision-making by up to 40%. In addition, Education Management Information System makes it easier for teachers to access online training and certification. However, obstacles such as limited infrastructure and lack of user training are still obstacles in the implementation of this system. Optimizing Education Management Information System requires improving infrastructure, continuous training, system integration, and strengthening data management policies to support the digitalization of madrasah education more effectively and sustainably.Keywords: Education Management Information System; Administrative Services; Teacher Professional Development; Madrasah Digitalization AbstrakPenelitian ini bertujuan untuk menganalisis implementasi Education Management Information System (EMIS) di Madrasah, mengidentifikasi tantangan dalam penerapan, serta mengevaluasi dampaknya terhadap layanan administrasi dan pengembangan profesional guru. Penelitian ini menggunakan metode mixed-method dengan pendekatan sequential explanatory. Data kuantitatif dikumpulkan melalui kuesioner dan dianalisis menggunakan uji korelasi, sedangkan data kualitatif diperoleh melalui wawancara untuk memperdalam temuan penelitian. Hasil penelitian ini menunjukkan bahwa Education Management Information System meningkatkan efesiensi administrasi, mengurangi kesalahan pencatatan hingga 35%, serta mempercepat pengambilan keputusan hingga 40%. Selain itu, EMIS mempermudah akses guru terhadap pelatihan dan sertifikasi daring. Namun, kendala seperti keterbatasan infrastruktur dan kurangnya pelatihan pengguna masih menjadi hambatan dalam implementasi sistem ini. Optimalisasi Education Management Information System memerlukan peningkatan infrastruktur, pelatihan berkelanjutan, integrasi sistem, serta penguatan kebijakan pengelolaan data guna mendukung digitalisasi pendidikan madrasah secara lebih efektif dan berkelanjutan.